1998
DOI: 10.1080/08039489850139382
|View full text |Cite
|
Sign up to set email alerts
|

Involuntary psychiatric hospital treatment among 12- to 17-year-olds in Finland: A nationwide register study

Abstract: Sourander A, Korkeila J, Turunen M-M. Involuntary psychiatric hospital treatment among 12-to 17-year-olds in Finland: A nationwide register study. Nord J Psychiatry 1998;52:367 -371. Oslo. ISSN 0803-9488.Information on involuntary psychiatric hospital treatment of all 12-to 17-year-old minors in 1990 and 1993 in Finland was collected from the national hospital discharge register. Involuntary treatment was associated with older age, psychosis diagnosis, and treatment in adult psychiatric ward. Treatment year, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 2 publications
1
16
0
1
Order By: Relevance
“…The strongest predictor for involuntary hospitalisation was having intellectual disability (OR 15·74, 95% CI 10·82–22·90). 27 Sourander and colleagues 39 also found that a diagnosis of psychosis and older age (15–17 years vs 12–14 years) were significantly associated with involuntary hospitalisation on multivariate analysis, controlling for gender, whether or not it was a first admission, whether they were admitted to an adult or adolescent unit, and the treatment year. On stepwise multiple logistic regression analysis, So and colleagues 38 found that any DSM-IV Axis 1 diagnosis, high risk of suicide, danger to others, previous compulsory care, and lack of motivation or compliance all predicted involuntary rather than voluntary hospitalisation.…”
Section: Resultsmentioning
confidence: 95%
“…The strongest predictor for involuntary hospitalisation was having intellectual disability (OR 15·74, 95% CI 10·82–22·90). 27 Sourander and colleagues 39 also found that a diagnosis of psychosis and older age (15–17 years vs 12–14 years) were significantly associated with involuntary hospitalisation on multivariate analysis, controlling for gender, whether or not it was a first admission, whether they were admitted to an adult or adolescent unit, and the treatment year. On stepwise multiple logistic regression analysis, So and colleagues 38 found that any DSM-IV Axis 1 diagnosis, high risk of suicide, danger to others, previous compulsory care, and lack of motivation or compliance all predicted involuntary rather than voluntary hospitalisation.…”
Section: Resultsmentioning
confidence: 95%
“…(Kaltiala‐Heino, Korkeila, Tuohimäki, Tuori, & Lehtinen, 2000; Richer‐Rossler & Rossler, 1993; Salize & Dressing, 2004; Sanquienti, Samuel, Schwartz, & Ropetson, 1996; Tuohimäki et al, 2003). There are limited national studies based on adolescent population which deals with involuntary treatment (Kaltiala‐Heino, 2004; Sourander et al 1998; Worall et al, 2004). The two Finnish nation‐wide studies Sourander et al (1998) and Kaltiala‐Heino (2004) were based on hospital discharge registers, which limits the reliability of the results.…”
Section: Introductionmentioning
confidence: 99%
“…The number of hospital beds for adolescents, in contrast to other psychiatric beds, has increased, but they are still neither sufficient nor equally distributed among regions. Minors still have to be treated in adult psychiatric wards (19), even if this is prohibited by Finnish law (Table 1), and adolescents have to wait for too long for both hospital and outpatient treatment. It now appears that the demand for psychiatric services among adolescents is much higher than that estimated by the Task Force in 1987 (although the estimation was then considered to be too high).…”
Section: Discussionmentioning
confidence: 99%